Gender and sex hormones influence the response to trauma and sepsis: potential therapeutic approaches (Clinics, 2006)
Several clinical and experimental studies have demonstrated gender dimorphism in immune and organ responsiveness and in the susceptibility to and morbidity from shock, trauma, and sepsis. In this respect, cell-mediated immune responses have been shown to be depressed in males following trauma-hemorrhage, whereas they were aintained/enhanced in proestrus females. Furthermore, sex hormones have been shown to be responsible for this gender-specific immune response following adverse circulatory conditions. More specifically, studies indicate that androgens produce immunodepression following trauma-hemorrhage in males. In contrast, female sex steroids appear to exhibit immunoprotective properties following trauma and severe blood loss. With regard to the underlying mechanisms, receptors for sex hormones have been identified on various immune cells suggesting direct effects of these hormones on the immune cells. Alternatively, indirect effects of sex hormones, ie, modulation of cardiovascular responses or androgen- and estrogen-synthesizing enzymes, might contribute to gender-specific immune responses. Recent studies indicate that sex hormones, eg, dehydroepiandrosterone (DHEA), also modulate the function of peripheral blood mononuclear cells in surgical patients. Thus, the immunomodulatory properties of sex hormones/receptor antagonists/sex steroid synthesizing enzymes following trauma-hemorrhage suggests novel therapeutic strategies for the treatment of immunodepression in surgical patients.